Thermal effect in hydrodynamic lubrication of line contacts - Piezoviscous effect neglected - Ghosh M.K.; Gupta K. (My University, 2025)
Thermal effect in high-speed rolling element bearings has been investigated numerically following a computationally efficient method developed by Elrod and Brewe [11]. Viscous shear heating effects on both film thickness and rolling friction are investigated for a line-contact geometry assuming fully flooded lubrication. Thermal load-carrying capacity and rolling friction of the line contact have been numerically calculated for varying rolling speeds from 5 to 40 m/s and dimensionless film thickness between 10-4 and 10-3. Results indicate marked influence of viscous shear heating on the load-carrying capacity, film thickness and rolling traction at high rolling speeds. Neglecting thermal effect at high rolling speeds would lead to gross overestimation of load capacity, film thickness and traction. Results are presented for pressure and temperature distribution within the contact for various rolling speeds and film thicknesses. © 1998 Elsevier Science Ltd.